Pengaruh Penilaian Kinerja Pegawai terhadap Prestasi Kerja dengan Kepuasan Kerja sebagai Variabel Intervening - Sudiaatmaja, I. Putu; Fitriani, Lili Karmela; Djuniardi, Dede (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The performance of State Civil Apparatus (ASN) significantly contributes to the effective and efficient implementation of bureaucracy. Several factors can influence ASN performance, particularly within the environment of the Kuningan District Secretariat. The use of the SIJAPATI application as a performance assessment tool plays a crucial role in enhancing ASN performance. Additionally, job satisfaction also theoretically impact performance. This study aims to examine the effects of performance assessment on ASN performance, mediated by job satisfaction, both partially and simultaneously. The research employs a quantitative descriptive method, with data collected through questionnaires and analyzed using the SEM-PLS method with the SmartPLS application. The findings indicate that performance assessments, both directly and indirectly mediated by job satisfaction, have a significant positive effect on performance.. These findings provide insights to enhance the effectiveness and efficiency of organizational performance within the Kuningan.